PEMBELAJARAN TEKS EKSPLANASI DENGAN METODE JIGSAW PADA PESERTA DIDIK KELAS XI TP SMK NEGERI 5 PEKANBARU SEMESTER 2 TAHUN PELAJARAN 2017-2018 - Reza Yetti (Departement of Mathematics Education, 2018)
In daily learning activity, students in vocational school are often difficult to master the subject class of Bahasa Indonesia. Addition to that, students prefer to learn the major class subject due to most of the teacher still using conventional learning method during the class ie: always using old lecture method. That impacted to students irresponsible attitude ie: lack of serious and inactive during the class. One of basic competence that need to be implemented is teamwork in analyzing, comparation, and inteprete the text explanation. This basic competence need a responsible attitude and team work among students to master the class learning. Supporting the above cause, this research class act journal try to present the Bahasa Indonesia learning method that can help students easily to master the subject. The learning method called jigsaw method. This method intended to empowered the responsible attitude and team work among the students. Also to grow the condusif learning environment.